2018
DOI: 10.1038/s41598-018-19360-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced TRBP phosphorylation enhances its interaction with PKR to regulate cellular survival

Abstract: Transactivation response element RNA-binding protein (TRBP or TARBP2) initially identified to play an important role in human immunodeficiency virus (HIV) replication also has emerged as a regulator of microRNA biogenesis. In addition, TRBP functions in signaling pathways by negatively regulating the interferon-induced double-stranded RNA (dsRNA)-activated protein kinase (PKR) during viral infections and cell stress. During cellular stress, PKR is activated and phosphorylates the α subunit of the eukaryotic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 59 publications
(73 reference statements)
1
20
0
Order By: Relevance
“…One of the first reported functions of PACT and TRBP is to modulate the PKR activity. Earlier studies proposed that PACT directly binds PKR and activates the PKR kinase activity in the absence of dsRNA (172)(173)(174), while TRBP inhibits PKR by directly binding to PKR and/or PACT (175)(176)(177). A homozygous missense mutation (P222L) in PACT was shown to cause hyperactivation of PKR and early-onset dystonia DYT16 (178), supporting the role of PACT in PKR modulation.…”
Section: Pact and Trbpmentioning
confidence: 92%
“…One of the first reported functions of PACT and TRBP is to modulate the PKR activity. Earlier studies proposed that PACT directly binds PKR and activates the PKR kinase activity in the absence of dsRNA (172)(173)(174), while TRBP inhibits PKR by directly binding to PKR and/or PACT (175)(176)(177). A homozygous missense mutation (P222L) in PACT was shown to cause hyperactivation of PKR and early-onset dystonia DYT16 (178), supporting the role of PACT in PKR modulation.…”
Section: Pact and Trbpmentioning
confidence: 92%
“…Not only PACT (PD3), but also TRBP is phosphorylated. TRBP binds and inhibits PKR more proficiently, when it is phosphorylated upon oxidative stress (Chukwurah & Patel, ) or during the mitotic phase in cell cycle (Kim et al, ). PKR is led to activation in these two conditions (Kim et al, ; Pyo et al, ) and TRBP phosphorylation prevents hyper‐activation of PKR, whose physiological significance appears to be the restriction of PKR activity under the tolerance level so that cells survive these conditions.…”
Section: Cellular Proteins For Pkr Regulationmentioning
confidence: 99%
“…However, the high level of post-translational modifications and regulation of the protein indicated that PKR activity does not necessarily have to correspond to the amount of its messenger RNA. In fact, numerous proteins have been described as regulating their activity (e.g., PACT, trans-activation response (TAR) RNA binding protein (TRBP), nucleophosmin (NPM)) [4,7,8,[46][47][48] and several post-translational modifications have been showed by SUMOylation and ISGylation, among others [49,50]. Nc886 has been described as a PKR inhibitor, being the inhibition of PKR/NF-kB in correlation with its tumour suppressor activity.…”
Section: Discussionmentioning
confidence: 99%